(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2013)
The article surveys the evidence for nomothesia procedures in the twenty years after the end of the Lamian war. It argues that fourth-century nomothesia could not survive the constitutional reforms imposed by Antigonus. Its procedures were later replaced by the individual action of the nomothetes Demetrius of Phalerum, who at the same time imposed on the Assembly the check of nomophylakes who took over the powers of the graphe paranomon and the graphe nomon me epitedeion theinai. Finally, after the restoration of democracy in 307, nomothetai reappeared for the last time, but were not, like before 322, in charge of voting on new proposals and enacting new legislation. They were special magistrates, possibly introduced by Demetrius Poliorcetes, in charge of proposing new laws to the Assembly for the purpose of reforming the constitution after the regime of Demetrius of Phalerum. After this last appearance of nomothetai in the late fourth century, in the third century no recognizable specific nomothesia procedure survived, and laws were enacted by the Assembly like decrees. The reason for the disappearance of nomothesia, it is argued, must be understood both in the context of the evolution of the relevant institutions, and in that of the abuse of the relevant terminology by Macedonian-controlled regimes at the end of the fourth century. L’articolo discute le fonti rilevanti per la ricostruzione delle procedure di nomothesia nei vent’anni successivi alla guerra Lamiaca e argomenta che la nomothesia, nella versione comune nel quarto secolo, non sopravvisse alle riforme costituzionali imposte da Antipatro. Le sue procedure furono dopo il 317 soppiantate dall’azione individuale di Demetrio di Falero, che assunse il ruolo di nomoteta e impose sull’Assemblea il controllo di un gruppo di nomophylakes con poteri che un tempo erano stati esercitati attraverso la graphe paranomon e la graphe nomon me epitedeion theinai. Dopo la restaurazione della democrazia ad opera di Demetrio Poliorcete un gruppo di nomoteti fa capolino per l’ultima volta nelle fonti. Il loro ruolo tuttavia non è quello di approvare le proposte di legge, come avveniva perima del 322, ma quello di proporre nuove leggi all’Assemblea, allo scopo di riformare la costituzione dopo la caduta di Demetrio di Falero. La loro istituzione negli ultimi anni del quarto secolo è probabilmente da collegare all’azione esplicita di Demetrio Poliorcete. Dal terzo secolo in poi non c’è alcuna traccia di una procedura separata di nomothesia: le leggi vengono probabilmente approvate dall’Assemblea allo stesso modo dei decreti. Nella conclusione si sostiene che la ragione della scomparsa della nomothesia vanno cercate tanto nell’evoluzione intrinseca delle procedure di nomothesia lungo il quarto secolo quanto all’abuso di questa terminologia da parte di vari regimi filomacedoni negli ultimi anni del quarto secolo.